Peningkatan Performansi Industri Kecil Pembuat Moulds Melalui Pengembangan CNC Retrofit Milling Untuk Meningkatkan Ketelitian Produk - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
A survey of several small-scale mould maker industries has identified two main stage of machining process in making a mould: rough-cutting and fine-cutting. The process technologies for roughing are milling, turning, and drilling/threading/boring. The process technologies for fine-cutting are Electric Discharge Machine (EDM) and grinding. Most of companies use a conventional milling machine for roughing due to limited capacity in using Computer Numerical Control (CNC) machine or limited budget to invest a CNC machine. In order to contribute in reducing of manufacturing cost and lead-time, the purpose of this research is to identify the small-scale mould maker industries problems, to identify the capability of CNC retrofit milling to solve that problems, and to develop a prototype of CNC retrofit milling system. Kata kunci: small-scale mould maker industries, rough-cutting, CNC retrofit milling